2005
DOI: 10.1271/bbb.69.583
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of Rosmarinic Acid in Intestinal Caco-2 Cell Monolayers

Abstract: The absorption characteristics of rosmarinic acid (RA) were examined by measuring permeation across Caco-2 cell monolayers using an HPLC-electrochemical detector (ECD) fitted with a coulometric detection system. RA exhibited nonsaturable transport even at 30 mM, and the permeation at 5 mM in the apical-tobasolateral direction, J ap!bl , was 0.13 nmol/min/mg of protein. This permeation rate is nearly the same as that of 5 mM chlorogenic acid (CLA) and gallic acid, which are paracellularly transported compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 33 publications
6
75
1
Order By: Relevance
“…The cells were seeded at a density of 1 Â 10 5 /cm 2 and grown in Transwell inserts with a semipermeable membrane coated with type I collagen, as previously reported. [4][5][6][7][8]12,13) The integrity of the cell layer was evaluated by measuring the transepithelial electrical resistance (TER) with Millicell-ERS equipment (Millipore, Billerica, MA, USA). A monolayer with a TER value of more than 300 Ácm 2 was used for the transepithelial transport experiments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were seeded at a density of 1 Â 10 5 /cm 2 and grown in Transwell inserts with a semipermeable membrane coated with type I collagen, as previously reported. [4][5][6][7][8]12,13) The integrity of the cell layer was evaluated by measuring the transepithelial electrical resistance (TER) with Millicell-ERS equipment (Millipore, Billerica, MA, USA). A monolayer with a TER value of more than 300 Ácm 2 was used for the transepithelial transport experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of p-coumaric or salicylic acid in this extract was estimated by using HPLC-ECD equipment fitted with an ESA coulometric detection system (ESA, Boston, MA, USA) as described in previous studies. [4][5][6][7][8]12,13) In brief, to measure p-coumaric acid, chromatographic separation was performed in a C18 column (ODS150, MC Medical, Tokyo, Japan) with mobile phase A (solvent A) of 50 mM sodium acetate containing 5% methanol (pH 3.0) and mobile phase B (solvent B) of 50 mM sodium acetate containing 40% acetonitrile and 20% methanol (pH 3.5). Eight electrode detector potentials (from 0 to 700 mV in increments of 100 mV) were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transport of hydroxycinnamates from the intestinal lumen to the plasma involves the simultaneous transport of hydrogen ions. Studies have shown that the MCAT is involved in the transport of hydroxycinnamates and their metabolites into epithelial cells (Konishi et al, 2003, Konishi & Kobayashi, 2004, Konishi, 2005, Konishi & Kobayashi, 2005.…”
Section: Uptake Of Phenolic Acids From the Intestinal Lumenmentioning
confidence: 99%